2018
DOI: 10.1002/adem.201800351
|View full text |Cite
|
Sign up to set email alerts
|

Solution Treatment Study of Inconel 718 Produced by SLM Additive Technique in View of the Oxidation Resistance

Abstract: The additive manufacturing concept for the production of complex near net shape metal parts is obtaining increasing attention due to the possibility of producing assembled and/or complex parts allowing optimal design and saving time and cost. The possibility to use the free design of Selective Laser Melting (SLM) techniques for the fabrication of complex 3D components using high performing, although difficult to work, materials such as Ni superalloys is really attractive. The particular process conditions that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 54 publications
(64 reference statements)
1
29
0
Order By: Relevance
“…The e in the as-built condition usually exhibits epitaxial growth of columnar grains columnar or cellular dendrites along the built direction, owing to the high cooling rates process (10 6 K/s [19,26]) and the heat dissipation direction, i.e., vertically through the 21,27]. et al [25,28] studied the microstructure of IN718 parts fabricated by PBF-LB in as-built treated conditions, revealing carbides, Laves phases, and segregations; therefore, heat e crucial to homogenize the microstructure. Li et al [13] studied the microstructure of phase) rich in Ni, Cr, and Fe, which is strengthened by the precipitation of metastable Metals 2019, 9, x FOR PEER REVIEW semifinished or finished products in the aerospace, automo industries [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The e in the as-built condition usually exhibits epitaxial growth of columnar grains columnar or cellular dendrites along the built direction, owing to the high cooling rates process (10 6 K/s [19,26]) and the heat dissipation direction, i.e., vertically through the 21,27]. et al [25,28] studied the microstructure of IN718 parts fabricated by PBF-LB in as-built treated conditions, revealing carbides, Laves phases, and segregations; therefore, heat e crucial to homogenize the microstructure. Li et al [13] studied the microstructure of phase) rich in Ni, Cr, and Fe, which is strengthened by the precipitation of metastable Metals 2019, 9, x FOR PEER REVIEW semifinished or finished products in the aerospace, automo industries [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Calandri et al [25,28] semifinished or finished products in the aerospace, automotive, biomedical/medical, and energy industries [6][7][8][9][10]. Diverse metals AM techniques exist, and the most adopted in the industry are Powder Bed Fusion (PBF) and Directed Energy Deposition (DED), as for the classification by the ISO/ASTM 52900 (2015) international standard.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sanviemvongsak et al [55] concluded that EBM, LBM and wrought Inconel 718 followed quasi-parabolic oxidation rates. Other studies [59] [60] found that SLM Inconel 718 specimens exposed for extended time ranges at 850°C have a parabolic oxidation rate resulted from the formation of a dense, protective, and stable oxide scale on the surface of the alloy.…”
Section: Oxidation Of Ni-based Superalloys and Inconel 718mentioning
confidence: 93%